PERANAN PENDIDIKAN TECHNOPRENEURSHIP UNTUK PEMBANGUNAN BERKELANJUTAN: STUDI KONSEPTUAL - Kosasih, Wilson; Ahmad, Ahmad; S., Lithrone Laricha; Utama, Didi Widya (Universitas Katolik Parahyangan, 2016)
This paper describes a technological business incubation model, developing integrated curriculum with technopreneurship education, as well as the involvement of Industrial Engineering of Tarumanagara University to create technology startup ecosystem. University holds the important role for enhancing technopreneurs in Indonesia. Academics or researchers as technology transfer agents, are responsible to disseminate technology entrepreneurship education broadly. Eventually, technological business incubator will able to accelerate commercialization of innovations or inventions from university researchs.